Patients' views on the use of an Option Grid for knee osteoarthritis in physiotherapy clinical encounters: An interview study. (4th August 2017) - Kinsey, Katharine; Firth, Jill; Elwyn, Glyn; Edwards, Adrian; Brain, Katherine; Marrin, Katy; Nye, Alan; Wood, Fiona
Abstract: Background: Patient decision support tools have been developed as a means of providing accurate and accessible information in order for patients to make informed decisions about their care. Option Grids ™ are a type of decision support tool specifically designed to be used during clinical encounters. Objective: To explore patients' views of the Option Grid encounter tool used in clinical consultations with physiotherapists, in comparison with usual care, within a patient population who are likely to be disadvantaged by age and low health literacy. Methods: Semi‐structured interviews with 72 patients (36 who had been given an Option Grid in their consultation and 36 who had not). Thematic analysis explored patients' understanding of treatment options, perceptions of involvement, and readability and utility of the Option Grid. Results: Interviews suggested that the Option Grid facilitated more detailed discussion about the risks and benefits of a wider range of treatment options for osteoarthritis of the knee. Participants indicated that the Option Grid was clear and aided their understanding of a structured progression of the options as their condition advanced, although it was not clear whether the Option Grid facilitated greater engagement in shared decision making. Discussion and conclusion: The Option Grid for osteoarthritis of the knee was well received by patient participants who reported that it helped them to understand their options, and made the notion of choice explicit. Use of Option Grids should be considered within routine consultations.